"THE MAN WHO DOES NOT SLEEP": ON THE SPECIFIC INTERPRETATION OF THE RUSSIAN MYTH ABOUT DON QUIXOTE IN THE SERIES OF STORIES "THE INVENTIONS OF PROFESSOR WAGNER" BY A. BELYAEV - Daria V. Ponomareva (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2024)
The peculiarities of the interpretation of the Russian myth about Don Quixote in the series of stories by A. Belyaev "The Inventions of Professor Wagner" is revealed within the specifics of the image of the main character, a rebel, an impostor, an extra person, a wanderer who appears as a knight of science. Wagner, whose image goes back to the figure of a cultural hero, strives to transform the reality around him, literally perceived as material for creating a new better world. Ridiculing the past as a trickster, the hero affirms the future of the "golden age" as a demiurge. The quixoticism of Professor Wagner is a scientific service in the name of humanity, a daily and intense, like a feat, work of a scientist.